Carpe low-dose aspirin: the new anti-cancer face of an old anti-platelet drug. (17th November 2018) - Mitrugno, Annachiara; Sylman, Joanna L.; Rigg, Rachel A.; Tassi Yunga, Samuel; Shatzel, Joseph J.; Williams, Craig D.; McCarty, Owen J.T.
Abstract: Cancer metastasis is a dynamic process during which cancer cells separate from a primary tumor, migrate through the vessel wall into the bloodstream, and extravasate at distant sites to form secondary colonies. During this process, circulating tumor cells are subjected to shear stress forces from blood flow, and in contact with plasma proteins and blood cells of the immune and hemostatic system, including platelets. Many studies have shown an association between high platelet count and cancer metastasis, suggesting that platelets may play an occult role in tumorigenesis. This mini-review summarizes recent and emerging discoveries of mechanisms by which cancer cells activate platelets and the role of activated platelets in promoting tumor growth and metastasis. Moreover, the review discusses how aspirin has the potential for being clinically used as an adjuvant in cancer therapy.